Professor Emeritus Dr. Borut Belec: the importance of his work for the development of Maribor and Slovenian geography - Kolnik, Karmen; Konečnik Kotnik, Eva (Journal for Geography, 2015)
Presentation of the professional career of Professor Emeritus of the University of Maribor dr. Borut Belec and the importance of his work for the development of Maribor and Slovenian geography, as well as the broader international audience thereof, is on one hand very complex because of the diversity and richness of its research and teaching results, and on the other hand very challenging how to visualize something new because of  the many privies records.The present record is therefore not only a display of bibliographic information, but it is also illustrated with the reflections of Professor, which were recorded at an interview with the Jubilant in mid-October 2015. The four themes (education, career, research and teaching) are among other well-rounded findings, that described his work and importance.